Enhanced Reversibility of Li‐Rich Binary Oxide Cathodes through Synergistic Interfacial Regulation for Improved Charge Transfer Kinetics at High Depth of Charge/Discharge - Qing Zhang; Jiaoyang Cheng; Jinxin Cao; Fang Lian (ChemElectroChem)
Lithium‐rich manganese‐based oxides are accepted as a promising cathode material for high‐energy density batteries. However, they suffer from irreversible structural transformations and detrimental interfacial reactions, especially under deep charge/discharge states, causing severe voltage fade and capacity degradation. Herein, Li‐rich binary oxide Li1.16(Ni0.25Mn0.75)0.84O2 is proposed to dual‐coated by superionic conductor Li1.4Al0.4Ti1.6(PO4)3 and conductive polymer polyaniline, displaying nearly two orders of magnitude promotion for lithium ion transmission coefficient (10−9.5 cm2 S−1) at the end of charge/discharge. COMSOL Multiphysics simulation indicates the synergistic interfacial coating elevates the homogeneous distribution of lithium–ions and current density, improving utilization rates of lithium–ions, mitigating irreversible structural transformation, and suppressing the dissolution of transition metal ions and side reactions between the cathode and electrolyte. Therefore, Li1.16(Ni0.25Mn0.75)0.84O2 with the significantly promoted charge transfer kinetics exhibits greatly strengthened specific capacity of 293.6 mAh g−1 at 20 mA g−1 within the range of 2.0–4.8 V, with an increased initial Coulombic efficiency of 84.42% and capacity retention of 88.94% in 150 cycles, alongside with a low voltage decay (0.23 V within 150 cycles) and a high rate capability of 160 mAh g−1 at 5 C.